Advances in drug delivery systems, 6 : proceedings of the Sixth International Symposium on Recent Advances in Drug Delivery Systems, Salt Lake City, UT, U.S.A., February 21-24, 1993 - Anderson, James M. (Elsevier, 1994)
Advances in Drug Delivery Systems, 6.